The Entrepreneurial Orientation of Agricultural SMEs in the Fez-Meknes Region: A Qualitative Study - Lakbir, Abderrahman; Laaraussi, Amale; Bouayad, Abdelrhani (Transactions on Engineering and Computing Sciences, 2022)
The objective of this paper is to examine how entrepreneurial orientation (EO) manifests itself in the context of agricultural SMEs integrated into the value chain in the Fez-Meknes region. More specifically, we seek to know to what extent the dimensions of EO are expressed in agricultural SMEs in the Fez-Meknes region. To do this, we used a qualitative study of 15 agricultural SMEs, using the Nvivo software for data analysis. This study revealed that the dimensions of EO in agricultural SMEs in the Fes-Meknes region do not differ from those reported in the literature. The three dimensions of EO were demonstrated by the agricultural SMEs in the region in a manner similar to that reported in the literature. The SMEs interviewed demonstrated innovation, risk taking, and proactivity.